1991
DOI: 10.1073/pnas.88.23.10530
|View full text |Cite
|
Sign up to set email alerts
|

T lymphocytes inhibit the vascular response to injury.

Abstract: The proliferation of vascular smooth muscle cells is controlled by specific growth factors and cytokines acting in paracrine networks. Macrophage products such as the platelet-derived growth factor and interleukin 1 promote smooth muscle proliferation and are released in the arterial wall during atherosclerosis and repair processes. T lymphocytes are also present in vascular tissue, but their role in vascular growth control in vivo has been unclear. We now demonstrate that rats in which T lymphocytes have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
82
3
2

Year Published

1994
1994
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(93 citation statements)
references
References 32 publications
6
82
3
2
Order By: Relevance
“…Furthermore, Nilsson et al (6) demonstrated a 58% decrease in degree of atherosclerosis in rabbits immunized against oxidized or native LDL. Other animal studies have also suggested that T lymphocytes may have a protective role against atherosclerosis progression (7). Rats in which T lymphocytes have been eliminated by a monoclonal antibody treatment develop larger proliferative arterial lesions after balloon-catheter injury.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Nilsson et al (6) demonstrated a 58% decrease in degree of atherosclerosis in rabbits immunized against oxidized or native LDL. Other animal studies have also suggested that T lymphocytes may have a protective role against atherosclerosis progression (7). Rats in which T lymphocytes have been eliminated by a monoclonal antibody treatment develop larger proliferative arterial lesions after balloon-catheter injury.…”
Section: Discussionmentioning
confidence: 99%
“…For example, elimination of T lymphocytes with monoclonal antibodies resulted in larger proliferative lesions in balloon-catheterized rat aortas. 45 Cyclosporine treatment (which suppresses T cells) of hypercholesterolemic mice and rabbits also accelerated atherosclerosis. 46,47 MHC class I-deficient C57BL/6 mice, which lack cytolytic T cells and have impaired natural killer cell activity, also developed a 3-fold increase in lesions in the aortic valve region when fed a high-fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the scarce presence of T lymphocytes in the neointima formed as a consequence of balloon injury would not suggest that these cells would have a major impact on this type of lesion. Results from studies using athymic nude rats 46,47 or T lymphocyte-depleted rats 46 have given equivocal results concerning the role of T lymphocytes in the pathogenic process of balloon injury-induced neointimal proliferation. Thus, present and previous results taken together do not support a significant influence of T lymphocytes on neointimal proliferation in the artery after balloon injury.…”
Section: Discussionmentioning
confidence: 99%